Istinbath Hukum Imam Syafi’i dalam Pemecahan Kasus Pelecehan Seksual di Indonesia - Muh. Aqsho Che Athoriq. R; Ferdiansa Putra; Rangga Mahesa; Kurniati Kurniati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study examines the legal istinbath method applied by Imam Syafi'i, especially in the context of solving sexual harassment cases in Indonesia. Legal identity, which etymologically means the excavation of law by deep reasoning, is used to determine the law in matters that are not directly regulated by the Qur'an and Hadith. Imam Shafi'i, through his major works such as